1997
DOI: 10.2165/00007256-199723060-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Endurance Training on Reproductive Function in Male Runners

Abstract: Investigations on reproductive function in male athletes are not as abundant in the literature as the research available on female athletes. The primary reason for this is the absence of an obvious clinical sign indicative of an alteration in reproductive function in male athletes. While alterations in the reproductive status of female athletes may be easily detected by the loss of menstrual regularity, a distinctive clinical sign reflective of reproductive dysfunction in the male is not apparent. In male runn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 69 publications
1
52
0
1
Order By: Relevance
“…Several studies have shown a potential relationship of exercise to hormonal and seminological alterations. [4][5][6][7] The characteristics observed in the present case seem to be in accordance with previously published observations, 4-7,12 the triathlete did not show any alterations for sperm number or velocity but showed significant alterations in sperm morphology and a great degree of sperm DNA fragmentation. Significant alterations in morphology and sperm DNA fragmentation have been correlated with longer times to conception and less chances of live birth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies have shown a potential relationship of exercise to hormonal and seminological alterations. [4][5][6][7] The characteristics observed in the present case seem to be in accordance with previously published observations, 4-7,12 the triathlete did not show any alterations for sperm number or velocity but showed significant alterations in sperm morphology and a great degree of sperm DNA fragmentation. Significant alterations in morphology and sperm DNA fragmentation have been correlated with longer times to conception and less chances of live birth.…”
Section: Discussionsupporting
confidence: 92%
“…Some authors have even established a theory of a volume-threshold. 4 Previous studies have related triathlon practice to semen alterations. 5,6 This relationship has been observed to be related to training volume.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ironman triathletes have been shown to exhibit oxidative damage as a result of training and competition (39). We have mentioned the minimum running volume threshold (3,15); however, as we have mentioned already, volume is not the only training parameter to consider relative to reproductive function. All influential parameters must be studied carefully in the training context, and an increase in scrotal temperature and reactive oxygen species production, which are well known to adversely influence seminal plasma and spermatozoa, should be avoided or minimized.…”
Section: Discussionmentioning
confidence: 96%
“…Early investigations pointed to exercise volume as the variable most affecting reproduction, thus hypothesizing a volume threshold for reproductive disorders (14,15). Other authors have suggested that exercise intensity is equally deleterious to, or even more so than, volume on reproductive function (16,17).…”
mentioning
confidence: 99%
“…The authors remark that a particular level or degree of training must be surpassed before any clinical alterations become evident [41]. Other authors also supported this notion as they concluded from their findings that a volume threshold for the effect of training on sperm parameters and hormones does truly exist [13,42,43]. Such volume threshold has been observed both in running and in cycling.…”
Section: Pathological and Clinical Proofmentioning
confidence: 87%